La pena de muerte como elemento de control de la violencia; análisis del Derecho Comparado. - Quirola Rivadeneira, Harold Estéfano (2023)
This research work is based on a doctrinal and normative study of the death penalty as an element of violence, based on the observation of different legal regulations applied in different countries, sanctions process have to be approval by the obtained results. A good thesis statement for the death penalty and the primary rights and institutions involved in the defense of life and human dignity will be carried out, in addition how to deal with violence and its types in our society, as well as analyzing the rates of violence in some countries that impose his sanction. The research is basic, bibliographic, documentary, field, and descriptive, with a non- experimental design, carried out with a population of 29 people involved. A survey was used as a technique for data collection, which has made it possible to establish whether the death penalty as a purpose to control violence. As a result, it was determined that the application of the death penalty is a reality that has had a long record where this sanction has been sentenced, suspended and abolished in Constitutions and regulations in many States of the world, therefore. it´s not a positive agent to control violence in order to obtain social changes and progress in modern societies.